Seychelles : Request for an Extended Arrangement Under the Extended Fund Facility-Press Release; Staff Report; and Statement by the Executive Director for Seychelles. (IMF Staff Country Reports; Country Report ;, 2021)
Seychelles was hit hard by the COVID-19 crisis. The authorities reacted swiftly, by locking down the economy, thereby keeping infection and fatality rates low. However, the travel restrictions and global economic downturn triggered unprecedented economic contraction. The authorities responded with measures to mitigate the economic fallout on businesses and households. But the public debt ratio increased sharply, reflecting the primary balance deterioration, exchange rate depreciation, and GDP contraction. As soon as vaccines became available, Seychelles led the world in vaccination coverage and reopened its borders. With tourist arrivals bouncing back, a V-shaped recovery is now expected.